Design and Construction of Solar Bajakah Wood Root Dryer by Using Solar Power and Biomass Stove - Muhammad Ivanto; Wiranto Wiranto; Eka Eka; Muhammad Syahrullah; Herman Herman; Nugroho Karya Yudha (Universitas Darussalam Gontor, 2021)
Bajakah root dryer is a drying tool by utilizing solar energy using a collector as a heat absorber which uses solar energy as a heat source. Drying is a process of reducing relatively small water content continuously in a material. The solar dryer system consists of three main parts, namely the solar collector, drying chamber, and biomass stove. This Bajakah root dryer has a lot of potential in the process of drying the Bajakah roots because it can produce quality Bajakah roots and facilitate the drying process of the Bajakah roots itself. The purpose of this study was to obtain the optimal design of the Bajakah wood root dryer so that it could speed up the drying process. The implementation method used consists of problem assessment, tool design and design, tool making,data collection analysis, evaluation and report generation. The results of the measurement of water content using a humidity meter showed a decrease in water content, namely, from the experiment on drying the roots of the bajakah, it was declared dry for 9 hours with a decrease in water content of 52.7% using a collector, a decrease in water content of 35.6% for 5 hours using a biomass stove. and a decrease in water content of 49% for 15 hours by drying directly.